2021
DOI: 10.1161/strokeaha.121.034301
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ischemic Stroke in Patients With COVID-19

Abstract: Background and Purpose: Studies suggest an increased risk of adverse outcomes among patients with acute ischemic stroke (AIS) and coronavirus disease 2019 (COVID-19). Methods: Using Get With The Guidelines–Stroke, we identified 41 971 patients (AIS/COVID-19: 1143; AIS/no COVID-19: 40 828) with AIS hospitalized between February 4, 2020 and June 29, 2020, from 458 Get With The Guidelines–Stroke hospitals with at least one COVID-19 case and evaluated clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
3
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 10 publications
1
32
3
10
Order By: Relevance
“…This relationship seems to ring true when we use historical controls of either all-cause ischaemic stroke (non-COVID) or LVOs. We found that mortality was significantly higher than the Get With the Guidelines (GWTG) non-COVID ischaemic cohort (39.1% vs 27.6%) or when compared with the respective LVO study arms in MR CLEAN (37.8% vs 11.6%) 10 12. The North American cohort of our consortium (n=216) fared worse than the comparable global cohort (n=174) of Ntaios et al 11 in terms of both morbidity and mortality.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…This relationship seems to ring true when we use historical controls of either all-cause ischaemic stroke (non-COVID) or LVOs. We found that mortality was significantly higher than the Get With the Guidelines (GWTG) non-COVID ischaemic cohort (39.1% vs 27.6%) or when compared with the respective LVO study arms in MR CLEAN (37.8% vs 11.6%) 10 12. The North American cohort of our consortium (n=216) fared worse than the comparable global cohort (n=174) of Ntaios et al 11 in terms of both morbidity and mortality.…”
Section: Discussionmentioning
confidence: 57%
“…We found that mortality was significantly higher than the Get With the Guidelines (GWTG) non-COVID ischaemic cohort (39.1% vs 27.6%) or when compared with the respective LVO study arms in MR CLEAN (37.8% vs 11.6%). 10 12 The North American cohort of our consortium (n=216) fared worse than the comparable global cohort (n=174) of Ntaios et al 11 in terms of both morbidity and mortality. Conversely, we also observed lower rates of favourable outcomes (mRS 0–2) compared with the GWTG non-COVID ischaemic cohort (17.8% vs 39.5%).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…En un registro de ACV en Estados Unidos que incluyó a 1143 pacientes con COVID-19 y ACV concomitante, la mediana de edad fue de 65,3 años (RIC 61,4-67,6) años, una diferencia mediana de −6,0 años (IC 95% −12,3 a −1,4) con aquellos pacientes que cursaron un ACV pero sin COVID-19 en el mismo período. (52,(60)(61)(62) Se observó que los pacientes con ACV y COVID-19 presentaban menor frecuencia de hipertensión arterial previa, sin diferencias significativas en los otros factores de riesgo cardiovasculares. Se evidenció mayor presencia de oclusión de grandes vasos y mayor gravedad clínica manifestada por un score del National Institute of Health Stroke Scale (NIHSS) más elevado que en aquellos que no presentaron paralelamente infección por COVID-19.…”
Section: Características De Los Pacientes Y Pronósticounclassified